From Tapering to Tightening The Impact of the Fed's Exit on India - Basu, Kaushik 1952-; Eichengreen, Barry 1952-; Gupta, Poonam 1969- (The World Bank, 2014)
The "tapering talk" starting on May 22, 2013, when Federal Reserve Chairman Ben Bernanke first spoke of the possibility of the U.S. central bank reducing its security purchases, had a sharp negative impact on emerging markets. India was among those hardest hit. The rupee depreciated by 18 percent at one point, causing concerns that the country was heading toward a financial crisis. This paper contends that India was adversely impacted because it had received large capital flows in prior years and had large and liquid financial markets that were a convenient target for investors seeking to rebalance away from emerging markets. In addition, India's macroeconomic conditions had weakened in prior years, which rendered the economy vulnerable to capital outflows and limited the policy room for maneuver. The paper finds that the measures adopted to handle the impact of the tapering talk were not effective in stabilizing the financial markets and restoring confidence, implying that there may not be any easy choices when a country is caught in the midst of rebalancing of global portfolios. The authors suggest putting in place a medium-term policy framework that limits vulnerabilities in advance, while maximizing the policy space for responding to shocks. Elements of such a framework include a sound fiscal balance, sustainable current account deficit, and environment conducive to investment. In addition, India should continue to encourage relatively stable longer-term flows and discourage volatile short-term flows, hold a larger stock of reserves, avoid excessive appreciation of the exchange rate through interventions with the use of reserves and macroprudential policy, and prepare the banks and firms to handle greater exchange rate volatility